Science in the making: 1930s citizen science on the BBC. Issue 3 (3rd May 2020) - Jones, Allan
ABSTRACT: During 1931–1933 several BBC radio broadcasts invited listeners to participate in what would now be termed 'citizen science' experiments. Scientists broadcast on a research topic, and asked for relevant data and observations from listeners. Most of these broadcasts were part of the Science in the Making series. Topics investigated ranged across natural history, meteorology, auditory perception, dreams and social science. One Science in the Making broadcast resulted in an article in a refereed academic journal. This article describes these broadcasts, the listeners' role, and the outcomes of the series. It situates them in the context of the BBC's adult education provision, and examines their educational and scientific contributions. Although the broadcasts were considered successful, they were short-lived. The article investigates reasons for this. It also looks at the reasons for the demise of inter-war adult education provision at the BBC during the later 1930s.